Drug loaded nanoparticle coating on totally bioresorbable PLLA stents to prevent in‐stent restenosis. Issue 1 (22nd November 2016) - Zhao, Jian; Mo, Zhichao; Guo, Fangfang; Shi, Donglu; Han, Qian Qian; Liu, Qing
Abstract: Biodegradable polymer poly (dl ‐lactide) (PDLLA) has been used as drug coating material for drug‐eluting stents due to its excellent biocompatibility and sustained drug release ability. However, the uniform thin layer drug eluting coating on a stent not only inhibits the blood vessel's smooth muscle cell overgrowth but also delay the endotheliation process which is often associated with the occurrence of acute thrombosis. Therefore, in this study, we developed a novel coating method using PDLLA nanoparticles (NPs) as a coating to overcome this issue. The average 300 nm sized sirolimus‐loaded PDLLA nanoparticles were prepared by a conventional emulsion solvent evaporation method. A low temperature plasma polymerization technology to graft hydrophilic polymers on to poly (l ‐lactide) stent was used to increase the surface coating efficiency of nanoparticles on the stent. Results showed that sirolimus‐loaded nanoparticles can be successfully coated on to the stents with sustained drug release properties. In vitro cell culture study showed the drug loaded nanoparticle coating effectively inhibited the proliferation of smooth muscle cells while still allowed a faster proliferation of endothelial cells, suggesting that the new NP coated bioresorbable stents have the potential to reduce both the occurrence of in‐stent restenosis and acute thrombosis. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 88–95, 2018.